Literature Review of the Green Building Concept of the Minister of PUPR RI Regulation Number 21 of 2021 concerning Evaluation Performance Building Building Green - Noviyanto, Okta; Agung Wahyudi Biantoro (Engineering And Technology Journal, 2024)
The green building concept has been adopted as the main approach in the development of this project. The purpose of this final project is to analyze and implement the green building concept based on the Regulation of the Minister of Public Works and Public Housing Number 21 of 2021 concerning Building Performance Assessment. In the initial stage, a literature study was conducted to understand the principles and important aspects of the green building concept in detail to understand the requirements and criteria that must be met in the implementation of this concept. Evaluation was conducted to assess the level of compliance with applicable regulations. In the implementation stage, it includes the selection of environmentally friendly materials, optimization of energy use through the installation of solar panels and the use of energy-saving equipment, efficient water management, and utilization of recycling and organic waste. The results of this final project are expected to provide a deep understanding of the implementation of the green building concept. It is also hoped that there will be recommendations and steps for improvement that can improve efficiency and environmental sustainability within this housing.